Revitalization of Palabe Bungo in Character Education and Early Childhood Communication Development through an Ethnopedagogical Approach - Indhra, Feerlie Moonthana; Anshori, Muhammad; Mananghaya, Michael Escaros; Chaw, Ei Phyu (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study aims to explore the role of palabe bungo in character education and the development of early childhood communication skills through an ethnopedagogical approach. Using a naturalistic qualitative method, this study was conducted in the context of the Bungo community with a direct observation approach, in-depth interviews, and documentation of Palabe practices in early childhood education environments. The data collected were in the form of oral narratives, social interactions, and children's verbal and non-verbal expressions when participating in the delivery of Palabe. The results of the study indicate that Palabe Bungo plays a role as a means of internalizing character values such as honesty, cooperation, tolerance, and respect for others through interactive and contextual storytelling. In addition, Palabe also contributes to developing children's communication skills by encouraging active participation in conversations, enriching vocabulary, and training the ability to listen and express ideas verbally. This study recommends the integration of Palabe in the early childhood education curriculum as an effort to preserve local culture as well as an effective learning strategy in strengthening children's character and communication from an early age.